2018
DOI: 10.1038/s41598-018-28675-5
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study of Cell Wall Structure and its Mechanical Properties of C3H and HCT RNAi Transgenic Poplar Sapling

Abstract: This research focused on the cell wall structure and its mechanical properties of down-regulated Coumaroyl shikimate 3-hydroxylase (C3H) transgenic poplar and down-regulated hydroxycinnamoyl CoA: shikimate hydroxycinnamoyl transferase (HCT) transgenic poplar (Populus alba × P. glandulosa cv ‘84 k’). The wood samples with respect to microstructure, the longitudinal elastic modulus (MOE) and hardness of wood fiber secondary cell wall were investigated. The results show that the lignin contents in the two transge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Several parameters influence the degree of lignin reduction, such as the target gene and the degree of downregulation of the enzyme activity, which in turn depends on the efficiency of the silencing construct used, the size of the gene family, and redundancy within the gene family. Generally, the downregulation of the steps from C4H up to CCR results in a more dramatic reduction in lignin amount (Hu et al, 1999; Meyermans et al, 2000; Zhong et al, 2000; Li L. et al, 2003; Jia et al, 2004; Lu et al, 2004; Leplé et al, 2007; Coleman et al, 2008a,b; Bjurhager et al, 2010; Mansfield et al, 2012; Ralph et al, 2012; Min et al, 2014; Van Acker et al, 2014; Zhou et al, 2015, 2018; Saleme et al, 2017; Xiang et al, 2017) than downregulation of F5H , COMT and CAD (Van Doorsselaere et al, 1995; Baucher et al, 1996; Lapierre et al, 1999; Jouanin et al, 2000; Van Acker et al, 2014; Wang et al, 2018). Lignin reduction can be associated with an increase in S/G, such as in C3’H - (Coleman et al, 2008a; Ralph et al, 2012) and CCoAOMT -downregulated trees (Meyermans et al, 2000), or a decrease in S/G ratio such as in CSE- (Saleme et al, 2017), and COMT- downregulated trees (Van Doorsselaere et al, 1995; Lapierre et al, 1999; Jouanin et al, 2000).…”
Section: Engineering the Lignin Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Several parameters influence the degree of lignin reduction, such as the target gene and the degree of downregulation of the enzyme activity, which in turn depends on the efficiency of the silencing construct used, the size of the gene family, and redundancy within the gene family. Generally, the downregulation of the steps from C4H up to CCR results in a more dramatic reduction in lignin amount (Hu et al, 1999; Meyermans et al, 2000; Zhong et al, 2000; Li L. et al, 2003; Jia et al, 2004; Lu et al, 2004; Leplé et al, 2007; Coleman et al, 2008a,b; Bjurhager et al, 2010; Mansfield et al, 2012; Ralph et al, 2012; Min et al, 2014; Van Acker et al, 2014; Zhou et al, 2015, 2018; Saleme et al, 2017; Xiang et al, 2017) than downregulation of F5H , COMT and CAD (Van Doorsselaere et al, 1995; Baucher et al, 1996; Lapierre et al, 1999; Jouanin et al, 2000; Van Acker et al, 2014; Wang et al, 2018). Lignin reduction can be associated with an increase in S/G, such as in C3’H - (Coleman et al, 2008a; Ralph et al, 2012) and CCoAOMT -downregulated trees (Meyermans et al, 2000), or a decrease in S/G ratio such as in CSE- (Saleme et al, 2017), and COMT- downregulated trees (Van Doorsselaere et al, 1995; Lapierre et al, 1999; Jouanin et al, 2000).…”
Section: Engineering the Lignin Pathwaymentioning
confidence: 99%
“…While several modifications of the lignin amount and composition were shown to provide improvements in biomass processing, these modifications were often accompanied by a biomass yield penalty (Leplé et al, 2007; Wadenbäck et al, 2008; Wagner et al, 2009; Voelker et al, 2010; Stout et al, 2014; Van Acker et al, 2014; Sykes et al, 2015; Zhou et al, 2018). A recent metastudy perturbed 21 lignin biosynthesis genes in P. trichocarpa , and comprehensively integrated the results of transcriptomic, proteomic, fluxomic, and phenomic data of 221 lines.…”
Section: Engineering the Lignin Pathwaymentioning
confidence: 99%
“…PAL overexpression has been observed to negatively impact plant growth in transgenic poplar (Rueda‐López et al , 2017). HCT catalyzes the transfer of the caffeoyl moiety of 5‐ O ‐caffeoylquinate onto CoA (producing caffeoyl‐CoA and quinate) and transgenic poplar with downregulated HCT genes exhibit slower growth and thinner stems than wild‐type (Peng et al , 2014; Zhou et al , 2018). Two (putatively) activating SNPs were predicted in the HCT paralog PtHCT2 (Potri.018G105500), and both of these lie in the same interval on chromosome 18 (Chr18:13219799‐13252693) that was found to be significantly associated with levels of cis ‐ and trans ‐3‐ O ‐caffeoylquinic acid by GWAS and eQTL analysis (Zhang et al , 2018a).…”
Section: Resultsmentioning
confidence: 99%
“…The changes of lignin content and composition had no adverse effect on the growth of transgenic plants but increased the biomass of transgenic plants, such as stem diameter, plant height and internode length. Zhou et al (2018) found that when the lignin content of C3H and HCT transgenic hybrid poplars (P. alba × P. glandulosa '84 K') decreased, the phenotype of plants showed abnormal growth in height, diameter, and so on 42 . Su et al (2019) found that when the content of lignin reduced, the content of lignin deposited in the cell wall decreased, which easily led to the abnormal phenotype of tissue culture seedling 43 .…”
Section: Discussionmentioning
confidence: 99%